COMT Val158Met, but not BDNF Val66Met, is associated with white matter abnormalities of the temporal lobe in patients with first-episode, treatment-naïve major depressive disorder: a diffusion tensor imaging study - Hayashi K (Dove Medical Press, 2014)
Kenji Hayashi,1 Reiji Yoshimura,1 Shingo Kakeda,2 Taro Kishi,3 Osamu Abe,4 Wakako Umene-Nakano,1 Asuka Katsuki,1 Hikaru Hori,1 Atsuko Ikenouchi-Sugita,1 Keita Watanabe,2 Satoru Ide,2 Issei Ueda,2 Junji Moriya,2 Nakao Iwata,3 Yukunori Korogi,2 Marek Kubicki,5 Jun Nakamura1 1Department of Psychiatry, 2Department of Radiology, University of Occupational and Environmental Health, Kitakyushu, Japan; 3Department of Psychiatry, Fujita Health University, Toyoake, Japan; 4Department of Radiology, Nihon University School of Medicine, Tokyo, Japan; 5Psychiatry Neuroimaging Laboratory, Brigham and Women's Hospital, Harvard Medical School, Boston, MA, USA Abstract: We investigated the association between the Val158Met polymorphism of the catechol-O-methyltransferase (COMT) gene, the Val66Met polymorphism of the brain-derived neurotrophic factor (BDNF) gene, and white matter changes in patients with major depressive disorder (MDD) and healthy subjects using diffusion tensor imaging (DTI). We studied 30 patients with MDD (17 males and 13 females, with mean age ± standard deviation [SD] =44±12 years) and 30 sex- and age-matched healthy controls (17 males and 13 females, aged 44±13 years). Using DTI analysis with a tract-based spatial statistics (TBSS) approach, we investigated the differences in fractional anisotropy, radial diffusivity, and axial diffusivity distribution among the three groups (patients with the COMT gene Val158Met, those with the BDNF gene Val66Met, and the healthy subjects). In a voxel-wise-based group comparison, we found significant decreases in fractional anisotropy and axial diffusivity within the temporal lobe white matter in the Met-carriers with MDD compared with the controls (P<0.05). No correlations in fractional anisotropy, axial diffusivity, or radial diffusivity were observed between the MDD patients and the controls, either among those with the BDNF Val/Val genotype or among the BDNF Met-carriers. These results suggest an association between the COMT gene Val158Met and the white matter abnormalities found in the temporal lobe of patients with MDD. Keywords: catechol-O-methyltransferase, brain-derived neurotrophic factor, 3-methoxy-4-hydroxyphenylglycol, homovanillic acid